Impacts of shed orientation on behavioural pattern, physiological changes and semen quality in HF X Sahiwal bulls (Indian Journal of Animal Production and Management, 2024)
The present study was conducted to assess the effect of two sides of North-South oriented shed with  open area in East and West directions on microclimatic variables, physiological & behavioural responses  and semen quality in Frieswal bulls. Adult breeding bulls (24) were distributed equally into East (GE) and  West (GW) facing opening sides of the shed. All the bulls were kept in individual pens under loose housing  system and were managed with uniform management practices. The average THI values during hot-dry  and hot-humid seasons were in the various levels of thermal stress in both the groups. During hot-dry and  hot-humid seasons, physiological responses in GW bulls were higher in the afternoon than in the morning  values, however, in GE bulls rectal temperature and respiration rate increased significantly in the afternoon  Sperm concentration was higher (p
Keywords: Behaviour; Crossbred bull; Housing; Physiological parameters; Semen